Consciousness of emotions and action selection. (2016) - Gainotti, Guido
Abstract: The domain of emotions corresponds to the consciousness model proposed by Morsella et al. The action schemata unconsciously activated by spontaneous emotions are indeed automatically selected from a small number of innate operative patterns, whereas behavioral responses selected at the cognitive level of emotional processing consist of strategic plans, leading to a conscious integration of goal-directed actions.